Buildings and semantics data models and web technologies for the built environment - Pauwels, Pieter; McGlinn, Kris (CRC Press/Balkema, 2023)
"The built environment has been digitizing rapidly and is now transforming into a physical world that is at all times supplemented by a fully web-supported and interconnected digital version, often referred to as Digital Twin. This book shows how diverse data models and web technologies can be created and used for the built environment. Key features of this book are its technical nature and technical detail. The first part of the book highlights a large diversity of IT techniques and their use in the AEC domain, from JSON to XML to EXPRESS to RDF/OWL, for modelling geometry, products, properties, sensor and energy data. The second part of the book focuses on diverse software solutions and approaches, including digital twins, federated data storage on the web, IoT, cloud computing, and smart cities. Key research and strategic development opportunities are discussed for distributed web-based building data management, IoT integration and cloud computing. This book will serve as a guide and reference for experts and professionals in AEC computing and digital construction including Master students, PhD researchers, and junior to senior IT-oriented AEC professionals"--
Includes bibliographical references and index. - Description based upon online resource; title from PDF title page (viewed August 8st, 2022)
Keywords: Building -- Data processing; Semantic Web; Construction; Informatique; Web sémantique; COMPUTERS / Information Technology; TECHNOLOGY / Construction / Estimating; TECHNOLOGY / General; Building; Data processing